The Ecopoetics of Reparation: Energy, Air and Cosmos in Marie Darrieussecq’s Tom est mort - McCaffrey, Enda (Dalhousie French Studies, 2020)
This article establishes that reparation from grief is a process of “working through” trauma in which death is a catalyst for a re-imagination of the human form. “Working through” trauma comes about in different ways in Tom est mort. It manifests itself firstly as a process “outside” Judeo-Christian and socio-cultural signifiers and outside traditional limits of cognition and subjectivity. Darrieussecq views reparation as a process of nonanthropocentric and anthropogenic relationality (with other species and other non-human phenomena) in which new coalitions and affinities offer an alternative post-human ontology founded in the reduction and dissolution of human form into atoms and particles. Secondly, reparation finds an ecopoetic continuity and sustainability in the narrator’s proximity to and approximation with the physics and spherical production of motion (energy, air, cosmos) and the reparative possibilities posed by this physics to traditional, psychic forms of communication. Darrieussecq’s vision is the hidden energy that operates in space around us. It is a knowledge of the hidden that comes from an acknowledgement of human redundancy in the face of the planet’s eco-vitality.